Des offrandes pour une petite fille. Analyse sémantique de l’assemblage coroplathique de la tombe 1427 d’Akanthos. - Huysecom-Haxhi, Stéphanie (O T I V M, 2024)
Grave 1427 from the Akanthos necropolis, discovered in 1979, is particularly remarkable for its funerary assemblage which includes figurative terracottas of different iconographical types, ceramic vases, including several perfume vases, pieces of adornment and astragals. All these artefacts form what can be called a funerary kit, maybe here a maiden kit, whose various pieces are signs charged with values that create meaning and explain their presence in this precise context and with the deceased for whom they were chosen and have been put together. It is the meaning of this particular kit and the various pieces of information that it can transmit about the identity of the deceased that we will try to highlight here, by proposing a semiotic analysis of the different categories of objects, and in particular the types of terracotta figurines. Comparison with similar documents from other contexts, both iconographic and archaeological, will enrich our thinking too.